2009
DOI: 10.1242/jcs.051482
|View full text |Cite
|
Sign up to set email alerts
|

Coronin 2A regulates a subset of focal-adhesion-turnover events through the cofilin pathway

Abstract: Precise control of cell-matrix adhesion is necessary for cell migration to occur. Fibroblasts lacking paxillin (PXN) or focal adhesion kinase (FAK), two core focal-adhesion components, display aberrant adhesion and decreased cell motility in vitro. Embryos deficient in genes that encode these proteins also lack proper mesoderm formation leading to embryonic lethality (Ilic et al., 1995;Hagel et al., 2002). In many types of cancer cell, focal adhesion proteins display either modulated protein expression or inap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…This is again in line with the report from Tang and Ostap, who showed that GFP-fused myo1b, a rat myosin I, localized along the cell periphery but not along stress fibers [60]. Distinct intracellular localizations of members of the same family of actin binding proteins have been reported for calponin-homology proteins [79], coronin [80], tropomyosin [81] and talin [82]. Notably, distinct intracellular localizations along specific actin-containing structures were also observed with the GFP-fused, isolated ABDs of Dictyostelium α-actinin and filamin, both of which are calponin homology proteins [79].…”
Section: Discussionsupporting
confidence: 91%
“…This is again in line with the report from Tang and Ostap, who showed that GFP-fused myo1b, a rat myosin I, localized along the cell periphery but not along stress fibers [60]. Distinct intracellular localizations of members of the same family of actin binding proteins have been reported for calponin-homology proteins [79], coronin [80], tropomyosin [81] and talin [82]. Notably, distinct intracellular localizations along specific actin-containing structures were also observed with the GFP-fused, isolated ABDs of Dictyostelium α-actinin and filamin, both of which are calponin homology proteins [79].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, actin filaments stabilize under tension, decreasing both spontaneous depolymerization rates 124 and reducing their sensitivity to severing by cofilin 125 . As actin scaffolds are essential for focal adhesion stability, this effect can also influence the lifetime of focal adhesions 126 .…”
Section: Molecular Aspects Of Mechanotransductionmentioning
confidence: 99%
“…Thus, a commonly used surrogate marker for cofilin activity in vivo is the generation of actin free barbed ends (46,55), although barbed ends might also arise from other mechanisms (45). Compared with WT cells, Swap-70 Ϫ/Ϫ BMMCs are impaired in reducing the number of actin free barbed ends upon SCF stimulation (Fig.…”
Section: Swap-70 Hinders Cofilin Severing Activity On Actin Filaments-mentioning
confidence: 99%